Photoperiod Extension Enhances Sexual Megaspore Formation and Triggers Metabolic Reprogramming in Facultative Apomictic Ranunculus auricomus - Klatt, Simone; Hadacek, Franz; Hodač, Ladislav; Brinkmann, Gina; Eilerts, Marius; Hojsgaard, Diego; Hörandl, Elvira (Frontiers in Plant Science, 2016)
Abstract • • Meiosis, the key step of sexual reproduction, persists in facultative apomictic plants functional to some extent. However, it still remains unclear how and why proportions of reproductive pathways vary under different environmental stress conditions. We hypothesized that oxidative stress mediates alterations of developmental pathways. In apomictic plants we expected that megasporogenesis, the stage directly after meiosis, would be more affected than later stages of seed development. • To simulate moderate stress conditions we subjected clone-mates of facultative apomictic Ranunculus auricomus to 10 h photoperiods, reflecting natural conditions, and extended ones (16.5 h). Reproduction mode was screened directly after megasporogenesis (microscope) and at seed stage (flow cytometric seed screening). Targeted metabolite profiles were performed with HPLC−DAD to explore if and which metabolic reprogramming was caused by the extended photoperiod. • Prolonged photoperiods resulted in increased frequencies of sexual vs. aposporous initials directly after meiosis, but did not affect frequencies of sexual vs. asexual seed formation. Changes in secondary metabolite profiles under extended photoperiods affected all classes of compounds, and c. 20% of these changes separated the two treatments. Unexpectedly, the renowned antioxidant phenylpropanoids and flavonoids added more to clone-mate variation than to treatment differentiation. Among others, chlorophyll degradation products, non-assigned phenolic compounds and more lipophilic metabolites also contributed to the dissimilarity of the metabolic profiles of plants that had been exposed to the two different photoperiods. • The hypothesis of moderate light stress effects was supported by increased proportions of sexual megaspore development at the expense of aposporous initial formation. The lack of effects at the seed stage confirms the basic assumption that only meiosis and sporogenesis would be sensitive to light stress. The concomitant change of secondary metabolite profiles, as a systemic response at this early developmental stage, supports the notion that oxidative stress could have affected megasporogenesis by causing the observed metabolic reprogramming. Hypotheses of genotype-specific responses to prolonged photoperiods are rejected.